PERAN GURU SEBAGAI FASILITATOR DALAM MENANAMKAN KARAKTER PEDULI LINGKUNGAN MELALUI PROGRAM ADIWIYATA DI SDN PETIR 1 KOTA TANGERANG - Eliana Rismayanti (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to (1) determine the implementation of the teacher's role as a facilitator in instilling the character of caring for the environment through the Adiwiyata programme carried out by the teacher; (2) knowing the supporting and inhibiting factors in implementing the Adiwiyata programme to instill the character of caring for the environment at SDN Petir 1 Tangerang City. This study uses descriptive qualitative research methods. Data collection techniques used are interviews, observation, and documentation. The results of this study are that the implementation of the role as a facilitator in instilling a caring character for the environment through the Adiwiyata programme is quite good, but there are still some activities that cannot be carried out, due to the pandemic. Supporting factors are the involvement of school residents, parents, and the government, supporting facilities and infrastructure, extracurricular activities that are integrated into environmental education. The inhibiting factor is that there are students who have not been able to apply a caring attitude to the environment and teachers can only direct some activities during online learning.